Case Report: Unveiling CHARGE syndrome: a neonatal case study with esophageal atresia and feeding difficulties - Gao, Fangjian; Li, Shuyan; Hu, Li; Zeng, Yali; Qiu, Jianwu (Frontiers in Pediatrics, 2025)
CHARGE syndrome is a collection of congenital malformations resulting from pathogenic variants that cause loss of function in the CHD7 gene. These malformations are characterized by coloboma, heart defects, atresia of the choanae, growth retardation, genital abnormalities, and ear abnormalities. We report a case of neonatal CHARGE syndrome, which presented with congenital esophageal atresia and feeding difficulties. Genetic analysis confirmed the presence of a mutation in the CHD7 gene. The diagnosis of CHARGE syndrome should be considered and confirmed through CHD7 gene sequencing in fetuses with esophageal atresia suspected by prenatal ultrasound, especially when combined with multiple malformations and feeding difficulties post-birth.